2019
DOI: 10.3390/vaccines7040173
|View full text |Cite
|
Sign up to set email alerts
|

Significant Interference with Porcine Epidemic Diarrhea Virus Pandemic and Classical Strain Replication in Small-Intestine Epithelial Cells Using an shRNA Expression Vector

Abstract: Porcine epidemic diarrhea (PED) re-emerged in China in 2010 and is now widespread. Evidence indicates that highly virulent porcine epidemic diarrhea virus (PEDV) strains belonging to genotype G2 caused a large-scale outbreak of diarrhea. Currently, vaccines derived from PEDV classical strains do not effectively prevent infection by virulent PEDV strains, and no specific drug is available to treat the disease. RNA interference (RNAi) is a novel and effective way to cure a wide range of viruses. We constructed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The invasion of pig intestinal epithelial cells by PEDV can cause enteritis in pigs of all ages and often lead to death of newborn piglets ( Wen et al, 2018 ). Although vaccines against PEDV exist, they are not optimal treatments in terms of safety and efficacy, resulting in large-scale infections still occurring ( Shi et al, 2019 ). Therefore, it is imperative to find new drugs against PEDV.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of pig intestinal epithelial cells by PEDV can cause enteritis in pigs of all ages and often lead to death of newborn piglets ( Wen et al, 2018 ). Although vaccines against PEDV exist, they are not optimal treatments in terms of safety and efficacy, resulting in large-scale infections still occurring ( Shi et al, 2019 ). Therefore, it is imperative to find new drugs against PEDV.…”
Section: Discussionmentioning
confidence: 99%
“…Two shRNAs targeting the NTD and one shRNA targeting the CTD of NPs showed dose-dependent inhibitory effects on both NP expression and PEDV replication in swine intestine epithelial cells. Particularly, all of the designed shRNAs had comparable antiviral function against the classical CV777 strain and the emerging LNCT2 strain [55] .…”
Section: Therapeutics Against Nps Of Domestic Animal Covsmentioning
confidence: 98%
“…In addition to chemical compounds, another study revealed that RNA interference targeting PEDV NPs could be effective in inhibiting virus replication. Shi et al ., analyzed 25 sequences of PEDV NPs from different countries and designed short hairpin RNAs (shRNAs) against regions conserved between classical and emerging PEDV [55] . Cell viability was not affected by transfection of plasmids expressing the shRNAs.…”
Section: Therapeutics Against Nps Of Domestic Animal Covsmentioning
confidence: 99%
“…Current vaccines against the classical CV777 strain of genotype 1 do not provide effective protection against Chinese highly virulent PEDV variant infections. Thus, Shi and colleagues [ 5 ] using a RNA interference (RNAi) approach, show that three short hairpin RNA (shRNA)-expressing plasmids directed against the viral nucleocapsid (N) present antiviral activities in intestine epithelial cells infected with a both classical CV777 and LNCT2 strains, and that these shRNAs markedly reduce viral replication of both of strains upon downregulation of N protein production; thus, these strategies, based on targeting viral processivity factors, may be feasible vaccine alternatives.…”
mentioning
confidence: 99%